Anonimisasi Data Penjualan Pakaian di Toko Online Menggunakan Metode K-Anonymity, L-Diversity, dan T-Closeness - Hidayat, Rahmat; Premananda, I Gusti Agung; Rakhmawati, Nur Aini (Teknik Informatika Universitas Pamulang, 2021)
The development of information technology will have an impact on the development of data. The existence of data might contain sensitive elements that are not intended to become public consumers. Anonymization is a technique that can be applied in publishing data with a different identity or anonymously. K-anonymity is an approach that can anonymization data. Besides that, the l-diversity and t-closeness approaches are also one of the advanced alternatives in data anonymization. The Mondrian algorithm can be implemented in k-anonymity. Therefore, we use the Mondrian algorithm for anonymizing clothing online transaction. The application of these methods can overcome the problem of data privacy contained in the dataset. The results obtained are that the application of the Mondrian algorithm in k-anonymity, l-diversity, and t-closeness has successfully performed data anonymization so that data cannot be consumed freely by other users.